(untitled) (TAMADDUN NURI JURNALI, 2024)
The aim of this research is to study and analyze the syntactic composition of scientific style. The importance of connective elements and syntactic precision is emphasized throughout the work. Qualitative and quantitative analysis methods are employed to examine various scientific texts. The results indicate that syntactic structures play a crucial role in clearly and logically expressing ideas in scientific writing.